2018
DOI: 10.1038/s41577-018-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

A cold-blooded view of adaptive immunity

Abstract: The adaptive immune system arose 500 million years ago in ectothermic (cold-blooded) vertebrates. Classically, the adaptive immune system has been defined by the presence of lymphocytes expressing recombination-activating gene (RAG)-dependent antigen receptors and the MHC. These features are found in all jawed vertebrates, including cartilaginous and bony fish, amphibians and reptiles and are most likely also found in the oldest class of jawed vertebrates, the extinct placoderms. However, with the discovery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
222
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(241 citation statements)
references
References 228 publications
(195 reference statements)
5
222
1
Order By: Relevance
“…8 and 9). Indeed, we would add to Mcfall-Ngai's [1] prescient framework quoted above and suggest that core bacteria that are more abundant in organisms with exclusively innate immunity may trade off this stability with more complex immune function during the evolution of adaptive immunity [68]. Indeed, top-down effects of immune function may be analogous to predation effects and promote maintenance of diversity by decreasing competition and allowing coexistence [79].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…8 and 9). Indeed, we would add to Mcfall-Ngai's [1] prescient framework quoted above and suggest that core bacteria that are more abundant in organisms with exclusively innate immunity may trade off this stability with more complex immune function during the evolution of adaptive immunity [68]. Indeed, top-down effects of immune function may be analogous to predation effects and promote maintenance of diversity by decreasing competition and allowing coexistence [79].…”
Section: Discussionmentioning
confidence: 89%
“…8b). While strongly correlated with host phylogeny, the complexity of adaptive immune systems across hosts based on a review by Flajnik [68] was developed into a matrix and score for each host class (Additional file 1: Table S3). Inclusion of the scale of adaptive immune system complexity in the path model for internal microbiomes indicated a significant direct association with microbial phylogenetic diversity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, a differentiated form of B cells, the plasmablasts, have been found as high as a 1000-fold increase, constituting up to 30% of the total PBMCs, in some cases even mimicking a plasma cell leukaemia during acute DENV infection (Gawoski and Ooi 2003;Balakrishnan et al 2011;Wrammert et al 2012). Most of these plasmablasts (70%) recognize DENV Most of DENV research has been performed in circulating blood cells from infected patients, in our study we evaluated the corresponding lymph nodes (DLNs) as crucial lymphoid organs evolved to facilitate the potential encounters between antigens and the low frequency of antigen-specific lymphocytes (Flajnik 2018). Using a previously established model of cutaneous DENV infection in immunocompetent mice (Yam-Puc et al 2015), we found by in situ evaluation and single-cell analysis, a nearly absent T cell proliferative response to DENV infection (measured by the expression of Ki-67), in both the CD4?…”
Section: Discussionmentioning
confidence: 99%
“…Vertebrate adaptive immunity is characterized by the Major Histocompatibility Complex (MHC) class I 444 and MHC class II proteins and their regulators. MHCI presents antigens derived from a cell's 445 intracellular environment, while MHCII presents antigens derived from material engulfed by 446 macrophages, B-cells or dendritic cells(Flajnik, 2018). We find 26 full length MHCI sequences from 447 the classic U-lineage and one sequence from the teleost-specific Z-lineage(Grimholt et al 2015; …”
mentioning
confidence: 90%